Online Zonation System on New Student Admissions During the Covid-19 Pandemic - Rachmadhany, Fitri; Sugiarto, Sugiarto; Matin, Matin (LPPM Undiksha, 2021)
This study aims to analyze the effectiveness of the implementation of online zonation system on new student admissions during the Covid-19 pandemic. During a pandemic, the entire PPDB process is carried out through one route. As for the difficulty, prospective students can come to school by sticking to health protocols. The research location is one of the favourite high schools. Primary data sources were obtained from in-depth interviews directly with informants. Secondary data sources are taken from books, journals, and other official documents from informants. The selection of informants was selected by purposive non-probability sampling: data collection techniques used online observation, in-depth interviews, and documentation. The data validity used source triangulation—this research analysis using descriptive method. The data collection technique was carried out through interviews with parents, school representatives, and related agencies and was also supported by literature studies related to school zoning policies. The results showed that the application of PPDB zoning was more effective online during the pandemic. Because it can minimize parents' arrival and optimize the functions of the existing PPDB system. The implementation of the school zoning policy caused turmoil in the community. Limited time for socialization, lack of understanding of the PPDB mechanism with the zoning system, and uneven educational standards are some of the obstacles in its implementation in the field.